2015
DOI: 10.3892/ol.2015.2999
|View full text |Cite
|
Sign up to set email alerts
|

Gestational choriocarcinoma with uterine serosal metastasis mimicking ruptured ectopic pregnancy: A case report

Abstract: Abstract. Primary gestational choriocarcinoma is commonly present in the uterus in cases of atypical genital bleeding. Symptoms similar to those of an ectopic pregnancy develop when an extra-uterine lesion is present in the abdominal cavity, and lesions have been detected in the ovaries and fallopian tubes in a number of cases. In the present study, we describe a patient with choriocarcinoma that metastasized to the uterine serosa and caused symptoms similar to those of an ectopic pregnancy. The patient was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Typically, choriocarcinoma disseminates extensively via hematogenous pathways, often correlating with distant metastases. A history of molar pregnancy is a prime risk factor for choriocarcinoma [5], a criterion met in the present case.…”
Section: Discussionmentioning
confidence: 76%
“…Typically, choriocarcinoma disseminates extensively via hematogenous pathways, often correlating with distant metastases. A history of molar pregnancy is a prime risk factor for choriocarcinoma [5], a criterion met in the present case.…”
Section: Discussionmentioning
confidence: 76%
“…A rare case report by Sinha M. et al describes a case of chorioadenoma destruens mimicking ruptured ectopic pregnancy [4]. A case report by Sakamoto Y et al reported gestational choriocarcinoma with uterine serosal metastasis mimicking ruptured ectopic pregnancy [5]. Ogu RN et al has reported a case of submucous uterine fibroid mimicking ruptured ectopic gestation [6].…”
Section: Resultsmentioning
confidence: 99%
“…Metastatic lesions may be isolated or multiple. Several miliary lesions and solitary or multiple nodules or masses can be observed and expressed as flaky, patchy, or cotton-like lesions [ 8 14 ]. These signs can occur alone or at the same time and can transform into each other in the development of the disease.…”
Section: Discussionmentioning
confidence: 99%